The emergence of 'citizenship' in popular discourse: the case of Scotland. Issue 8 (17th November 2019) - Hennebry-Leung, Mairin; Bonacina-Pugh, Florence
ABSTRACT: The 2014 Scottish Referendum gauged public opinion on the possibility of Scotland leaving the United Kingdom, raising significant questions about the legitimacy of claims to citizenship in the event of independence. Through a mixed methods survey, this study explored the ways in which citizenship emerged in popular discourse in the lead up to the Scottish referendum. Findings point to an emphasis in public discourse on a commitment to and participation in society, instead of the more traditional citizenship markers of ancestry, birthplace or residency. Data indicates a view of citizenship encompassing status and practice, while identity was framed in terms of more static notions of birthplace and ancestry. The salience of social participation was noticeably greater in respondents' assessment of others' potential Scottish citizenship than their own. Specifically, the study highlights the salience of relational aspects of citizenship in popular discourse, with an emphasis on social citizenship in preference to legal citizenship. The study constitutes a significant contribution to ongoing discussions about 'participatory citizenship' in the field of Citizenship studies, by providing much needed empirical data on social conceptualizations of citizenship.